The impact on the quality of life of physiotherapists in the Covid-19 pandemic front line (Research, Society and Development, 2022)
Faced with the pandemic of the new coronavirus (Covid-19), the professional physiotherapist has an important role within the context we are experiencing. In addition to the excessive and degrading work hours imposed on them, which makes their routines more stressful, concern with the quality of life of the professional involved is essential. In view of this, this study aimed to report the impact on the quality of life of physical therapists in the front line to the Covid-19 pandemic. The specific objectives were to assess sleep quality and correlate quality of life with the quality of sleep of physiotherapists in the front line of the Covid-19 pandemic. The population consisted of physiotherapists from the Hospital de Clínicas de Passo Fundo, Hospitalar Santa Terezinha - Erechim and Hospital de Caridade de Erechim, with a sample of thirteen physical therapists, of both sexes, with an average age of 29.5 years, who work on the front line of Covid-19 in the outpatient and ICU of the hospitals already mentioned. As results achieved, it can be seen that both hospitals had a regular self-assessment of quality of life, with higher scores in the environment domain (71.15%) and worse in the physical domain (48.63%). Regarding sleep quality, there was a presence of sleep disorder in 23.1% and poor sleep quality in 76.9%. There was a negative and moderate correlation between social relationships and sleep quality, and the other correlations were very weak. Thus, it is concluded through the results that the physical therapists who work on the front line of Covid-19 presented a regular quality of life and decreased quality of sleep.